Paediatric Strategy Forum for medicinal product development for acute myeloid leukaemia in children and adolescents: ACCELERATE in collaboration with the European Medicines Agency with participation of the Food and Drug Administration. (September 2020) - Pearson, Andrew. D.J.; Zwaan, C.Michel; Kolb, E.Anders; Karres, Dominik; Guillot, Julie; Kim, Su Young; Marshall, Lynley; Tasian, Sarah K.; Smith, Malcolm; Cooper, Todd; Adamson, Peter C.; Barry, Elly; et al.
Abstract: Purpose: The current standard-of-care for front-line therapy for acute myeloid leukaemia (AML) results in short-term and long-term toxicity, but still approximately 40% of children relapse. Therefore, there is a major need to accelerate the evaluation of innovative medicines, yet drug development continues to be adult-focused. Furthermore, the large number of competing agents in rare patient populations requires coordinated prioritisation, within the global regulatory framework and cooperative group initiatives. Methods: The fourth multi-stakeholder Paediatric Strategy Forum focused on AML in children and adolescents. Results: CD123 is a high priority target and the paediatric development should be accelerated as a proof-of-concept. Efforts must be coordinated, however, as there are a limited number of studies that can be delivered. Studies of FLT3 inhibitors in agreed paediatric investigation plans present challenges to be completed because they require enrolment of a larger number of patients than actually exist. A consensus was developed by industry and academia of optimised clinical trials. For AML with rare mutations that are more frequent in adolescents than in children, adult trials should enrol adolescents and when scientifically justified, efficacy data could be extrapolated. Methodologies and definitions of minimal residual disease need to be standardised internationally and validated as a new response criterion. Industry supported, academic sponsored platform trials could identify products to be further developed. The Leukaemia and Lymphoma Society PedAL/EUpAL initiative has the potential to be a major advance in the field. Conclusion: These initiatives continue to accelerate drug development for children with AML and ultimately improve clinical outcomes. Highlights: Introduction of innovative medicines into paediatric acute myeloid leukaemia (AML) needs to be accelerated. Trials of new agents in de novo  AML should be embedded in cooperative group trials. Prioritisation is required, as there are a limited number of deliverable studies. The PedAL/EUpAL Master Trial should accelerate the evaluation of novel drugs. Development of CD123-targeted drugs should be accelerated as a proof-of-concept.